2008
DOI: 10.1007/s11581-008-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical characteristics of (LiCl) x (P2O5)1 − x glass

Abstract: Homogeneous (LiCl) x (P 2 O 5 ) 1 − x glasses were synthesised using a melt-quenching method for x=0.1-0.6 in the interval of 0.05. The amorphous structure of the samples was evident by the X-ray diffraction spectrum. The short range structures of the binary phosphate samples were examined by Fourier transform infrared spectroscopy, whilst the density of the samples was measured as supportive data for the investigations. The results of refractive indices as measured using an ellipsometer reveal the homogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several studies [ [4] , [5] , [6] , [7] ] have shown that Li 2 O–P 2 O 5 glass is an excellent fast-conducting glass for Li + ions. One of the strategies embraced for augmenting conductivity involves introducing a doping salt, such as a metal halide (LiX, where X = Cl–, Br–, I–), into these glass compositions [ [8] , [9] , [10] ]. However, their poor thermal stability and mechanical properties limit their usefulness [ 11 , 12 ] because the addition of Li 2 O breaks the P–O–P bonds and allows the depolymerization of the glassy network.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [ [4] , [5] , [6] , [7] ] have shown that Li 2 O–P 2 O 5 glass is an excellent fast-conducting glass for Li + ions. One of the strategies embraced for augmenting conductivity involves introducing a doping salt, such as a metal halide (LiX, where X = Cl–, Br–, I–), into these glass compositions [ [8] , [9] , [10] ]. However, their poor thermal stability and mechanical properties limit their usefulness [ 11 , 12 ] because the addition of Li 2 O breaks the P–O–P bonds and allows the depolymerization of the glassy network.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, many phosphate glassy systems containing a metal oxide (Li, Na, Ag) glass modifier and a doping salt (LiCl) were investigated . The effect of the addition of a salt was studied for the first time in 1966 by Otto et al, who proposed an oxide glass which showed a remarkably high Li + ion conductivity, caused by the dissolution of Li 2 SO 4 and LiCl.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the past few decades, many phosphate glassy systems containing a metal oxide (Li, Na, Ag) glass modifier and a doping salt (LiCl) were investigated. [4][5][6] The effect of the addition of a salt was studied for the first time in 1966 by Otto et al, 7 who proposed an oxide glass which showed a remarkably high Li + ion conductivity, caused by the dissolution of Li 2 SO 4 and LiCl. These type of glasses, where a metal halide is mixed with a glass former, have shown further interest due to their potential application as inorganic vitreous electrolytes with high conductivity.…”
Section: Introductionmentioning
confidence: 99%